Correlation between plasma fibrin-fibrinogen degradation product values and CT findings in head injury. Issue 1 (January 1985) - Ueda, S; Fujitsu, K; Fujino, H; Sekino, T; Kuwabara, T
Abstract : Plasma fibrin/fibrinogen degradation product (FDP) determinations and CT scans were performed in 26 patients on the first, third, and seventh day after head injury. Plasma FDP concentrations were increased in the patients with cerebral contusion shown on CT scans, while the plasma FDP values were normal in the patients with various sized epidural haematomas. Furthermore, the plasma FDP elevation appeared to be more marked and more prolonged in the patients with severe contusion than in those with mild contusion. These findings suggest that the degree of the increase in plasma FDP is proportional to the amount of brain tissue destruction.